Riverine relations, affective labor and changing environmental subjectivity in Kerala, South India. Issue 140 (March 2023) - Sony, R.K.; Krishnan, Siddhartha
Highlights: This study extends the notion of environmentality to make a case for biopower emerging or exercised from below. Environmental subjectification does not always occur from above through environmental discourses and governance techniques. There are different pathways to environmental subjectification, which include embodied practices and affective labor. People's emotion, care, and affective relations with their immediate nature act as subjectivity-forming factors. Highlights the importance of having a prior affective relationship with nature in fostering environmental subjectivities. Abstract: Recent works in political ecology draw attention to affective ecologies that focus on lived experiences and fluid/relational subjectivities. The attention to affect and materiality grounded in vitalist ontology helps imagine new sociological futures and re-envision humanistic notions of agency. In this paper, we build on affective ecology and emotional political ecology literature to demonstrate how people's subjectivity is transformed through their lived experience of polluted waterscapes, memories of emotional and material engagement with their immediate nature, and affective labor practices to protect their rivers from pollution. Through sociological research conducted around two environmental protests in Kerala, we provide insights into local communities' engagement with the changed riverscape. Our analysis shows that formation of environmental subjects does not always occur through environmental discourses and governance techniques as the environmentality literature suggests. Rather, there are different pathways to environmental subjectification, which include embodied practices and affective labor. For activists involved in Eloor and Kathikudam movements in Kerala, India, their interactions with the river- an immediate nature in both cases- and the memories associated with it act as a central force in the becoming of people who care for the environment. We suggest that villagers' everyday involvement in movement work and struggle to protect rivers from pollution strengthen their individual and collective subjectivities.